Diagnostic Value of Hepatic Vein Ultrasound in Early Detection of Liver Cirrhosis: - Matinfard, Sedighe; Zare Marzouni, Hadi; Davachi, Behrooz; Rezazadeh, Mahdi; Salehi Milani, Mahmoud (Galen Medical Journal, 2018)
Background: Cirrhosis is a common disease that destroys liver cells, and it has various etiologies. The early diagnosis of cirrhosis can be effective in improving prognosis. Considering the availability and affordability of ultrasound devices throughout the world, in this study we evaluated the diagnostic value of hepatic vein ultrasound examination in the early detection of liver cirrhosis. Materials and Methods: In this study, 45 patients referred to the radiology department of Ghaem Hospital for liver biopsy were evaluated for changes in the hepatic veins under ultrasound with a transducer of 5-7MHz. One piece of the hepatic vein was selected for ultrasound, and the wall of hepatic veins was examined for straightness and uniformity of echogenicity. Subsequently, patients underwent biopsy by ultrasound guide.Â  Of all the study subjects, eight patients presented mild chronic hepatitis without fibrosis, four patients were diagnosed with fatty liver, and 33 patients had severe cirrhosis or chronic hepatitis with fibrosis. Results: Our results showed that hepatitis patients with or without fibrosis had irregular and wavy hepatic vein wall (impairment in straightness) with non-uniform echo (impairment in uniformity of echogenicity). While patients without hepatitis and cirrhosis, but diagnosed with fatty liver, had a smooth and regular hepatic vein wall with a uniform echo. Conclusion: The present study showed that hepatic vein examination in terms of echogenicity and straightness could be used to diagnose hepatitis, its severity as well as its course towards fibrosis and cirrhosis.Â [GMJ.2018;7:e1140]